The quantitative effect of the Thatcherism taxation programme: Computational experiments based on a dynamic general equilibrium model - Robbie Noel Wilson; Aleksandar Vasilev (Economics and Econometrics Research Institute (EERI), 2023)
This paper analyses the quantitative welfare effects of the Thatcherism taxation programme reforms. Modern macroeconomic techniques are put into application to the important historical fiscal reforms. The Paper provides details of the Thatcherism taxation reform, the changes in taxation rates and brackets. Through a dynamic general equilibrium model, the paper provides counter-factual growth rates. A comparison between the factual and counter-factual growth rates is given. The paper finds that through both welfare measures, that welfare increased due to the Thatcherism taxation program. These results will provide use and benefit for; policymakers, those studying the Laffer-Curve, those with supply-side economic ideas or beliefs, and those studying the economic, political, and historical period under the Thatcher government.
Keywords: E32; 330; Thatcher government; tax reform; general equilibrium; endogenous growthmodel; compensatory variation